Implementation of Principles of Biospheric Compatibility in the Practice of Ecological Construction in Ukraine - Chernyshev, Denys; Ivakhnenko, Iryna; Ryzhakova, Galyna; Predun, Konstantin (International Journal of Engineering and Technology, 2018)
The article considers current trends in ecological construction based on the principles of biospheric compatibility. The necessity of an integrated, multi-level approach to addressing the environmental safety of urbanized areas and the renovation of the urban environment is shown. Generalized indicators of biosphere compatibility of territories and the level of implementation of city functions are proposed, a method for calculating the components of the humanitarian balance is developed on the basis of a comprehensive analysis of existing methods for assessing pollution of the cityâ€™s environment and the adopted concept of improving the environmental safety of construction sites. The presented algorithm for monitoring the quality of the urban environment makes it possible to evaluate indicators of biosphere compatibility and to implement the reconstruction of natural and man-made systems based on biosphere-compatible technologies. Implementation of the expanded reproduction of the Biosphere and the creation of a comfortable living environment for the harmonious development of man; Improving the quality of life based on innovative biosphere-compatible resource-energy-efficient technologies ensures the positive dynamics of the components of the humanitarian balance of the Biotechnosphere, which increases the Life Potential of the Biosphere through the implementation of non-pathological programs of the city - programs of ecologo-oospherical transformations aimed at restoring disturbed humanitarian balance. In preparing these proposals, modern foreign experience was analyzed, and legal mechanisms for supporting economic actors in the field of ecological construction in the USA, Great Britain, Germany, Austria and the Nordic countries were studied.Â Â